2014
DOI: 10.5897/ajb2013.13373
|View full text |Cite
|
Sign up to set email alerts
|

Derangement of hemopoiesis and hematological indices in Khat (Catha edulis) - treated rats

Abstract: The purpose of this study was to identify the sub-acute toxic effects of Khat (Catha edulis) on hemopoiesis and hematological indices of white albino rats. Two groups, each of 10 rats, were used. In the experimental group, a hydro-ethanol extract of C. edulis was administered orally to rats, daily, in single doses of 500 mg/kg body weight, for for weeks. The control group received equivalent amounts of normal saline. Our results show, for the first time, that oral administration of C. edulis hydro-ethanol extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
3
10
2
Order By: Relevance
“…Khat had remarkable effects on the red blood cells. Notably, it induced anemia as depicted by the depletion of RBC and HCT ( Figure 2 ) in concert with findings in other studies on khat ( Ismaeel et al., 2014 ; Ketema et al., 2015 ). These results suggest the possibility of khat-induced RBC hemolysis and/or khat induced impairment of liver iron recycling function due to increased total bilirubin levels ( Figure 9 ) and histopathological findings ( Figure 13 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Khat had remarkable effects on the red blood cells. Notably, it induced anemia as depicted by the depletion of RBC and HCT ( Figure 2 ) in concert with findings in other studies on khat ( Ismaeel et al., 2014 ; Ketema et al., 2015 ). These results suggest the possibility of khat-induced RBC hemolysis and/or khat induced impairment of liver iron recycling function due to increased total bilirubin levels ( Figure 9 ) and histopathological findings ( Figure 13 ).…”
Section: Discussionsupporting
confidence: 89%
“…Khat-induced derangement of blood components has been observed in previous studies ( Alsalahi et al., 2012 ; Ismaeel et al., 2014 ); such derangements potentially lead to blood related syndromes. Khat had remarkable effects on the red blood cells.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Based on the extraction protocol followed, doses administered and model animal used, different authors reported the direct effect of khat on hematological parameters [23,24]. In our case, using methanol as extraction solvent and dose from 50-200 mg/kg in Swiss albino mice, khat has shown negative effect on total WBC and platelet counts, but not on other hematological parameters.…”
Section: Discussionmentioning
confidence: 66%